Family Support and Midwives Motivation for the First Stage of Labor - Siska Nawang Ayunda Maqfiro; Triany Laila Pelu (Universitas Aisyiyah Yogyakarta, 2023)
The first stage of labor is the longest duration compared to the second, third, and fourth stages. At this time requires extra energy because contractions occur that cause feelings of fear, anxiety, and excessive stress, triggering the release of non-epinephrine hormones that inhibit the work of oxytocin so that it can prolong the first stage of labor. The purpose of this study was to investigate the relationship between family support and the midwives's motivation for the first stage of labor progress in an Independent Midwifery Practice within working area of Kalumata Public Health Center, Ternate City. The population is woman who during the first stage of labor in an Independent Midwifery Practice in Ternate City. There were 30 samples in this research that have been selected by using quota sampling technique. The data were collected by using questionnaires and partographs. The results of multivariate analysis using logistic regression showed that the two independent variables, family support and midwife's motivation when correlated multivariate together showed that had not relationship with the progress of the first stage of labor with the significant value equal to 0,05 and more than 0,05 is 0,999. The progress of labor is multifactorial that related with each other and not independent. Although the woman had received support from her family and motivation from the midwife, if her self efficacy was low, that can make anxiety and increased intervention in labor. Support in labor should be a standard procedure that is planned to be provided by midwife to pregnant woman and their families before the signs and symptoms that labor has begun.